2009
DOI: 10.1016/j.psyneuen.2008.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of cocaine-seeking by progesterone treatment in female rats

Abstract: SummaryClinical research suggests that gender differences exist in cocaine dependence. Similarly, preclinical studies have shown that female rats exhibit higher response rates during cocaine self-administration, early extinction, and cocaine-primed reinstatement of drug-seeking. These effects are also estrous cycle dependent and inversely related to plasma progesterone, in that proestrus females (high progesterone) exhibit less cocaine-seeking, while estrous females (low progesterone) show the greatest cocaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 82 publications
7
67
1
Order By: Relevance
“…Thus, similar to female rats, drug-experienced women appear to devalue food (and perhaps other natural reinforcers) relative to taking drugs to a greater extent than men, which is likely a significant contributor to the more severe profile of cocaine dependence that women display. Future projects are required to assess the role of estrogen in cocaine choice in a more detailed fashion, as well as examine the effect of other ovarian hormones (eg, progesterone and its metabolite, allopregnanolone) on cocaine choice, as this ovarian hormone has been shown to decrease motivation for cocaine in single reinforcer studies (Feltenstein et al, 2009;Anker et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, similar to female rats, drug-experienced women appear to devalue food (and perhaps other natural reinforcers) relative to taking drugs to a greater extent than men, which is likely a significant contributor to the more severe profile of cocaine dependence that women display. Future projects are required to assess the role of estrogen in cocaine choice in a more detailed fashion, as well as examine the effect of other ovarian hormones (eg, progesterone and its metabolite, allopregnanolone) on cocaine choice, as this ovarian hormone has been shown to decrease motivation for cocaine in single reinforcer studies (Feltenstein et al, 2009;Anker et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the role of progesterone in drug-seeking behaviors has been mixed. Progesterone has been shown to be negatively correlated with drug-seeking behavior in cocaine-trained, female rats Feltenstein et al, 2009;Larson et al, 2007). However, it has been shown that the progesterone metabolite, allopregnanolone, can have both a stimulatory or inhibitory effect on ethanol intake depending on the dose administered and the drinking paradigm used (Ford et al, 2005;Janak et al, 1998;Morrow et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, levels of cocaine craving vary across the menstrual cycle (Fox et al 2008) with evidence to suggest that these levels are influenced by the ratio of estradiol to progesterone (Sinha et al 2007). Similar findings have been observed in animal models in which levels of cocaine-seeking vary across the estrous cycle with the highest levels observed during estrus (Kippin et al 2005;Kerstetter et al 2008;Feltenstein and See 2007;Feltenstein et al 2011), a period when there are higher levels of estradiol compared to progesterone (Feltenstein et al 2009). Results have also shown that the incubation effect, the progressive increase in cocaine-seeking over protracted abstinence (Grimm et al 2001), is heightened and prolonged in estrus females compared to males and to females in non-estrus phases (Kersetter et al 2008).…”
Section: Dose-dependent Efficacy Of Exercise To Attenuate Cocaine-seesupporting
confidence: 81%
“…This finding suggests that higher "doses" of exercise and/or environmental enrichment are required to compensate for hormonal influences during estrus (i.e. high estrogen levels as compared to progesterone; Feltenstein et al 2009) that would normally potentiate responding. In contrast, non-estrus females given prior limited access to a running wheel or extended access to a locked wheel demonstrated that less physical activity is required to reduce cocaine-seeking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation